A Model-Driven Approach for Mobile Business Intelligence - Duarte, David Monteiro (2016)
The concept of Mobile Business Intelligence is nowadays gaining prominence in business markets. With the emergence and evolution of mobile technologies such as smartphones and tablets, the users gain the opportunity to analyze the corporate information, anywhere and anytime, based on charts, tables and dashboards. However, there is also the question of how to provide the freedom to the user to build its own analytical components. This work will address the problem of developing a hybrid mobile solution towards the Business Intelligence domain, offering monitoring services and simultaneously addressing the problem of user empowerment, with easy configuration and semi-automatic generation of analytical widgets. To provide such capacity to the user, the proposed solution is based on the design of a Domain Specific Modeling Language, aligned with the Model-Driven Development approach and inspired by the Product Lines principles. The last part of this work is dedicated to evaluate the language usability based on an empirical test, executed by a set of subjects with different backgrounds of specialization. In this sense, we define two groups: end users and domain experts. The goal is to determine the extent to which the prototype can be used to empower the end users. As support for the analysis we have extracted a set of measures, alongside with the final appreciation from the domain experts group, composed by people currently working on Business Intelligence.